2021
DOI: 10.1080/1369118x.2021.1991976
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Glaring Gap’: practitioner experiences of integrating the digital lives of vulnerable young people into practice in England

Abstract: As young people rely increasingly on the internet to learn and socialise, the support they require becomes more complex. Some young people are more vulnerable online than others, such as young people in care or with Special Educational Needs. There is evidence that professionals working with vulnerable young people are ill-equipped to enhance children's safety online and support them through recovery if required. This research aims to explore the understanding, experience and processes among a range of senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Our results, particularly themes one (Breadth of the problem) and two (Working with OCSA), are similar to those found in other studies ( 33 , 38 43 ) in that practitioners acknowledged the growing number of CYP whose presentation included OCSA, but there were differences in how this was conceptualized, the importance they placed on it, and their responses to either a disclosure by the CYP or information provided by an earlier assessment and included in the referral process. In particular, there was a blurred boundary between practitioners who described discrete manifestations of OCSA and those who used a more inclusive definition of sexual crimes involving CYP that were enabled by technology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results, particularly themes one (Breadth of the problem) and two (Working with OCSA), are similar to those found in other studies ( 33 , 38 43 ) in that practitioners acknowledged the growing number of CYP whose presentation included OCSA, but there were differences in how this was conceptualized, the importance they placed on it, and their responses to either a disclosure by the CYP or information provided by an earlier assessment and included in the referral process. In particular, there was a blurred boundary between practitioners who described discrete manifestations of OCSA and those who used a more inclusive definition of sexual crimes involving CYP that were enabled by technology.…”
Section: Discussionsupporting
confidence: 92%
“…This study was replicated with a larger sample of 29 practitioners which similarly showed that practitioners demonstrated a limited and fragmented understanding of young people's online vulnerabilities and risks, with no integration of these issues into routine practice. The emphasis for practitioners was on identifying risk rather than understanding the experiences of young people, and there were no appropriate training, or assessment tools available to them ( 43 ). One response to a lack of training for practitioners has been the development of a short course designed to increase competencies and confidence in responding to the therapeutic needs of young people following online abuse ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research highlighted a lack of awareness and training among practitioners who often do not consider the online lives of their vulnerable young people (El-Asam et al, 2020, 2021b. This lack of specialist training was also evident in a study of psychiatry trainees, only 9.7% of whom had received digital risk training (Aref-Adib et al, 2020).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…While vulnerable children have received more attention from policy makers in recent years due to the regular collection of data by the Children's Commissioner for England, what motivates and influences the digital lives of these children and young people is less well understood by frontline services who work with them (El-Asam et al, 2020, 2021b. When explaining why vulnerable young people are more exposed to risk than others one might consider the Social Compensation Hypothesis, which suggests that those who perceive their offline social networks to be lacking seek to compensate through their online activities, for example through their social interactions (e.g., Livingstone et al, 2005;Peter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the other, they are frequently in contact with a myriad of differing professionals who, working with the child and their parent/guardians, create childcentred communities of support. The disjuncture here is that, despite connectivity being increasingly required of all citizens, and children with disabilities coming into frequent contact with a wide range of professionals, they receive less support navigating the Internet than their peers (Glencross et al, 2021;Livingstone et al, 2017;El-Asam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%